LEGISLATIVE AND PRACTICAL INITIATIVES TO CONTROL EXTREMISM IN SPORTS: SERBIAN EXPERIENCE - Tolvaishis, L.L.; Jovanovic, P. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze practical experience, progress and benefits of the extremism in sports control system in Serbia. Methods and structure of the study. We used the following criteria listed by the UN Office on Drugs and Crime to analyze the valid Serbian control system for extremism in sports: space security; social awareness; educational service; individual /group tolerance of extremism in sports; and youth empowerment service. Results and conclusion. The space security concept implies an institutional security system for the event attendants, with the relevant physical specifications of the secured space plus psychological, socio-cultural and political aspects including a facilitating social climate with trust, friendliness, hospitality, intolerance to violence, discrimination, hostility, harassment, discord and alienation. As things now stand in Serbia, the extremism in sports prevention initiatives and projects compliant with the five UN criteria are still underdeveloped and ineffective, whilst the extremism in sports is still controlled by the criminal and administrative codes. The efforts to implement the primary extremism in sports prevention projects focused on the school and young supporter communities are still non-systemic and inefficient. Most of such projects initiated by the Ministry of Education, municipal police departments, schools and non-governmental organizations are very limited in project areas and/ or timeframes. The local football clubs appear still unprepared to decisively contribute to the extremism in sports prevention initiatives.